Cadmium selenide microspheres as an electrochemical supercapacitor. (June 2017) - Pawar, Sachin A.; Patil, Dipali S.; Shin, Jae Cheol
Abstract: This paper reports the synthesis of cadmium selenide electrodes by simple and cost effective chemical bath deposition method for the electrochemical supercapacitors. In order to study the effect of deposition time onto the morphological and electrochemical performance of CdSe electrodes, the reaction time was varied from 2 h to 10 h. As the reaction time goes on increasing the voide-less uniform growth of the thin films with increased size and density of CdSe microspheres is observed from field emission microscopy study. The supercapacitive behavior of the prepared electrodes were analysed with the help of electrochemical impedance, cyclic voltammetry and charge/discharge measurements. The areal capacitance is found to increase from 0.30 mFcm −2 to 1.285 mFcm −2 with respect to the deposition time, this indicates the positive effect towards the electrochemical performance. Highlights: CdSe microspheres have been synthesized by CBD method. Effect of deposition time on morphological and electrochemical performance is studied. The supercapacitive behavior is studied using different electrochemical measurement techniques. The areal capacitance is found to increase from 0.30 mFcm −2 to 1.285 mFcm −2 with respect to the deposition time.